2016
DOI: 10.5005/jp-journals-10046-0051
|View full text |Cite
|
Sign up to set email alerts
|

Why Chronic Pain Patients are Misdiagnosed 40 to 80% of the Time?

Abstract: Researchers from Johns Hopkins Hospital have reported that 40%-80% of chronic pain patients are misdiagnosed. The leading causes for these errors are a failure to take a thorough and comprehensive history from the patient, and ordering the wrong tests. Typical testing errors are the use of anatomical tests to detect the physiological phenomenon of chronic pain, and a failure to understand the specificity and sensitivity of medical testing commonly in use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…One study has found that the diagnosis of chronic pain was overlooked by referring physicians in 66.7% out of 60 cases, which included peripheral nerve entrapment, radiculopathy, and TOS ( 219 ). Similar chronic pain studies revealed that 40% to 80% of patients were misdiagnosed ( 220 ). Misdiagnosis in chronic pain is a challenging, complex problem ( 221 , 222 ) that may be influenced by etiological uncertainty of this disorder as well as by relevant diagnostic bias and inertia.…”
Section: Implications For Chronic Pain Managementmentioning
confidence: 94%
“…One study has found that the diagnosis of chronic pain was overlooked by referring physicians in 66.7% out of 60 cases, which included peripheral nerve entrapment, radiculopathy, and TOS ( 219 ). Similar chronic pain studies revealed that 40% to 80% of patients were misdiagnosed ( 220 ). Misdiagnosis in chronic pain is a challenging, complex problem ( 221 , 222 ) that may be influenced by etiological uncertainty of this disorder as well as by relevant diagnostic bias and inertia.…”
Section: Implications For Chronic Pain Managementmentioning
confidence: 94%
“…First, considerations for Lune's physical and mental health challenges, and whether Lune might be eligible for reasonable accommodations (per the Americans With Disabilities Act [ADA]), are warranted. Studies suggest that chronic pain is often misdiagnosed (estimates of 40%-80% of patients; Hendler, 2016). Additionally, experiences of pain are more often underestimated and less likely to be treated for patients with diverse identities, including racial/ethnic diversity, gender diversity, and low socioeconomic status patients (e.g., Samulowitz et al, 2018;Summers et al, 2021;Trawalter et al, 2016).…”
Section: Vignette 6: Adapting To Chronic Painmentioning
confidence: 99%
“…Despite pain being one of the most common medical complaints, many patients still suffer from untreated or undertreated pain [11]. Approximately 100 million adults (or roughly 30% of adults) suffer from pain, with a misdiagnosis rate of up to 40-80% for chronic pain patients [12,13]. Pain can negatively impact quality of life when left untreated and can progress from an acute to a chronic condition, which results in considerable morbidity and mortality [14].…”
Section: Introductionmentioning
confidence: 99%